Searching for a Common Thrombo-Inflammatory Basis in Patients With Deep Vein Thrombosis or Peripheral Artery Disease - Kremers, Bram M. M.; Birocchi, Simone; van Oerle, Rene; Zeerleder, Sacha; Spronk, Henri M. H.; Mees, Barend M. E.; Luken, Brenda M.; ten Cate, Hugo; ten Cate-Hoek, Arina J. (Frontiers in cardiovascular medicine, 2019)
Inflammation and hypercoagulability play a pivotal role in venous thromboembolism and atherothrombosis. Since venous thrombosis increases the risk of atherothrombotic events and vice versa, common mechanisms may be involved. To elucidate the role of neutrophils and coagulation in the occurrence of atherothrombotic events in patients with a history of deep vein thrombosis (DVT or peripheral artery disease (PAD). We studied 115 patients from two cohorts (75 DVT, 40 PAD). From those with PAD, 20 patients had progressive disease; from those with DVT, 25 patients had a recurrent DVT and 25 suffered from post thrombotic syndrome (PTS); patients were age and sex matched to DVT and PAD patients without events. Markers of neutrophil recruitment (p-selectin) and activation [nucleosomes, human neutrophil elastase- α1anti-trypsin (HNE-AT)], an anti-inflammatory marker (Lipoxin A4) and a clotting activity marker (d-dimer), were measured with ELISA. Coagulation potential was analyzed by thrombin generation (CAT method). Higher nucleosome levels were found in DVT patients [11.3 U/mL (7.4-17.7)] compared to PAD patients [7.1 U/mL (5.1-13.8)], lower HNE-AT levels were found in DVT patients [33.4 ng/mL (23.5-40.5)] in comparison to PAD patients [158 ng/mL (88.1-283)]. No difference in nucleosome levels was found between DVT patients with cardiovascular (CV) events [12.6 U/mL (8.2-16.1)], and PAD patients with CV events [6.9 U/mL (4.9-11.2)]. Lipoxin A4 levels appeared to be significantly lower in DVT [2.4 ng/mL (1.7-4.8)] vs. PAD [35.6 ng/mL (16.6-80.1)], with similar results in DVT patients with CV events vs. PAD patients with CV events. Thrombin generation showed higher ETP [160.4% (141.1-215.4)], and peak height [292.1% (177.9-330)] values in DVT patients. D-dimer levels were significantly lower in the DVT cohort [330 ng/mL (220-550)] compared to the PAD cohort [550 ng/mL (369-959)]. In DVT patients, neutrophil activity does not appear to be an important driver of CV events. Although neutrophil activity is more pronounced in PAD, its effect is partly dampened by Lipoxin A4. Moreover, no associations were found between NET products and coagulation activity, suggesting that neutrophil activation does not play a pivotal role in the risk of thrombosis in either DVT or PAD.